2015
DOI: 10.1080/02701367.2015.1012578
|View full text |Cite
|
Sign up to set email alerts
|

On the Role of Proprioception in Making Free Throws in Basketball

Abstract: The results indicate that free-throw success is, at least partly, determined by players' ability to sense the position of the distal joints of their throwing upper limb. From a motor-control point of view, this suggests that basketball players may organize the compensatory behavior between the joints of their free-throwing arm on the basis of proprioception. From a practical point of view, it points toward new training techniques to enhance free-throwing efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
40
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 15 publications
4
40
0
1
Order By: Relevance
“…Proprioception also has a crucial role in balance control, and ankle proprioception is the most important aspect of balance (13). Because of the efficiency of the proprioception system, basketball players may organize compensatory behaviors with the joints of their upper limbs, which are used for shooting (35). Because of the lack of relationships between jump accuracy to specific heights (percentage and total errors methods) and maximum take-off force, this variable cannot be used to evaluate the efficiency of the proprioception system.…”
Section: Discussionmentioning
confidence: 99%
“…Proprioception also has a crucial role in balance control, and ankle proprioception is the most important aspect of balance (13). Because of the efficiency of the proprioception system, basketball players may organize compensatory behaviors with the joints of their upper limbs, which are used for shooting (35). Because of the lack of relationships between jump accuracy to specific heights (percentage and total errors methods) and maximum take-off force, this variable cannot be used to evaluate the efficiency of the proprioception system.…”
Section: Discussionmentioning
confidence: 99%
“…Among these techniques, quite eye, focusing attention, pre-performance routines, verbal feedback and modelling have been highlighted [9]. In addition, proprioception has been indicated to play a key role in FT [10]. On the other hand, less information is available about the effect of exercise intensity on FT accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…The role of proprioceptive training is highlighted in a series of studies conducted in different sports. In a study conducted on basketball players, Sevreza & Bourdin (2015) have found that success in free throws is, at least partly determined by the capacity of players to feel the position of the distal joints based on the proprioceptive impulses related to the wrist.…”
Section: Discussionmentioning
confidence: 99%